2003
DOI: 10.1038/sj.mp.4001263
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a high-risk haplotype for the dystrobrevin binding protein 1 (DTNBP1) gene in the Irish study of high-density schizophrenia families.

Abstract: A recent report showed significant associations between several SNPs in a previously unknown EST cluster with schizophrenia. 1 The cluster was identified as the human dystrobrevin binding protein 1 gene (DTNBP1) by sequence database comparisons and homology with mouse DTNBP1. 2 However, the linkage disequilibrium (LD) among the SNPs in DTNBP1 as well as the pattern of significant SNP-schizophrenia association was complex. This raised several questions such as the number of susceptibility alleles that may be in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
132
4
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 131 publications
(151 citation statements)
references
References 70 publications
(63 reference statements)
14
132
4
1
Order By: Relevance
“…In this study we sought to replicate association of AKT1 with schizophrenia in the ISHDSF, prompted by the susceptibility haplotype in this sample within the dysbindin (DTNBP1) gene (21). Although no single AKT1 marker showed association with disease, the data were consistent with global association of common alleles for selected SNP haplotypes including rs1130214, and a striking under-transmission of these haplotypes with the rare allele (T) at rs1130214.…”
Section: Discussionmentioning
confidence: 51%
“…In this study we sought to replicate association of AKT1 with schizophrenia in the ISHDSF, prompted by the susceptibility haplotype in this sample within the dysbindin (DTNBP1) gene (21). Although no single AKT1 marker showed association with disease, the data were consistent with global association of common alleles for selected SNP haplotypes including rs1130214, and a striking under-transmission of these haplotypes with the rare allele (T) at rs1130214.…”
Section: Discussionmentioning
confidence: 51%
“…As seen in several other studies of schizophrenia candidate genes, different samples tend to have different risk haplotypes, [38][39][40][41][42][43][44] including flipping of the risk and protective haplotypes of DTNBP1 gene between the ISHDSF 45 and German nuclear families 46 and other samples. 47,48 In this study, the two family samples identified the same risk and protective haplotypes, but in the case-control sample, the risk haplotype in the family samples become protective (underrepresented in the affected individuals).…”
Section: Discussionmentioning
confidence: 66%
“…We did see a trend towards association between dysbindin and better go/nogo performance. Interestingly, Fallgatter et al (2006), using a neurophysiological index of the same paradigm in a normal sample, also found evidence of association with two dysbindin SNP's previously associated with schizophrenia (Schwab et al, 2003;van den Oord et al, 2003). Investigation in a larger schizophrenia sample will be required to interpret the significance of these results.…”
Section: Discussionmentioning
confidence: 99%